2020
DOI: 10.1002/mrd.23431
|View full text |Cite
|
Sign up to set email alerts
|

Seeing is believing: Current methods to observe sperm acrosomal exocytosis in real time

Abstract: Acrosomal exocytosis (AR) is a critical process that sperm need to undergo to fertilize an egg. The evaluation of the presence or absence of the acrosome is usually performed by using lectins or dyes in fixed cells. With this approach, it is neither possible to monitor the dynamic process of exocytosis and related molecular events while discriminating between live and dead cells, nor to evaluate the acrosomal status while sperm reside in the female reproductive tract. However, over the last two decades, severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…4B) spermatozoa. Consistent with this finding, we observed that NEN and BAM15 had no effect on other ATP-dependent human sperm physiological processes, including the acrosome reaction, a necessary pre-fertilization exocytotic event (29,30) that exposes key fertilization receptors (31,32) (Fig. S4A – C), and human sperm hyperactivated motility (33) (Fig.…”
Section: Resultssupporting
confidence: 82%
“…4B) spermatozoa. Consistent with this finding, we observed that NEN and BAM15 had no effect on other ATP-dependent human sperm physiological processes, including the acrosome reaction, a necessary pre-fertilization exocytotic event (29,30) that exposes key fertilization receptors (31,32) (Fig. S4A – C), and human sperm hyperactivated motility (33) (Fig.…”
Section: Resultssupporting
confidence: 82%
“…As mentioned before, this co-staining advantage of TLFC opens up the possibility of combining additional fluorescent dyes to further explore other physiological parameters in sperm. For instance, the simultaneous assessment of [Ca 2+ ] i changes and the sperm’s Pg-induced acrosome exocytosis could be performed using the appropriate combination of fluorescent labels (e.g., Fluo3 and a fluorescent-labeled lectin, respectively) [ 61 ]. This evaluation is of special interest, since the level of Pg-triggered acrosome exocytosis is yet another parameter associated with capacitation and fertility [ 30 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this goal, epididymis was collected from all groups and was incubated in 1 mL PBS at 37°C for 15 min. Then, they were resuspended in a total volume of 1.8 mL, after adding 800 µL of 10% formalin buffer solution, and then stored on ice until analysis with a ow cytometry under illumination in the range of the 360-400 nm that is related to eGFP uorescence (32). A four-color FACS Calibur ow cytometer (BD bioscience) was used to collect the data and data were analyzed using the CellQuest Pro software package (BD bioscience).…”
Section: Flow Cytometry Of Enhanced Green Uorescent Protein Expression (Egfp)mentioning
confidence: 99%